Relationship between anemia, hypoalbuminemia, vitamin D deficiency and quality of life in advanced non-small cell lung carcinoma patients at tertiary hospital in Bali - Ekaruna, I. B. P.; Suryana, Ketut; K., Jasminarti D.; Candrawati, N. W.; Arisanti, N. L. P. Eka; Sajinadiyasa, I. G. K.; Rai, I. B. N. (International Journal of Advances in Medicine, 2021)
Background: The main purpose of treatment in patients with advanced lung cancer is more emphasizing on prolonging survival and improving the patient's quality of life (QOL). Micronutrient deficiency has an impact on the patient's QOL. The purpose of this study was to analyse the relationship between biochemical parameters of nutrient deficiency with QOL in patients with advanced non-small cell carcinoma (NSCLC) at Sanglah hospital. Methods: A cross sectional study was conducted in Sanglah general hospital on March-June 2021. Hemoglobin, albumin, and 2.5 (OH) D levels were obtained from patient's serum. The participant’s QOL was measured with EQ-5D-3L questionnaire. Bivariate analysis using chi-square test or Fisher's exact test, and multivariate analysis using logistic regression. Results: A total of 80 participants were included in this study, and 55% had poor QOL. Seventy percent participants had anemia, 36.3% had hypoalbuminemia, and 26.3% had vitamin D deficiency. The QOL of patients with advanced stage NSCLC was significantly associated with hypoalbuminemia (p=0.000) and vitamin D deficiency (p=0.044). Multivariate analysis showed that the most influential factor on the QOL of patients with advanced stage NSCLC was hypoalbuminemia (AOR 9.158; 95% CI 2.150-30.001; p=0.003). Conclusions: Hypoalbuminemia and vitamin D deficiency were significantly related with QOL of advance NSCLC patients. No relationship was found between anemia and the QOL of advance NSCLC patients. Hypoalbuminemia was the most influential factors related to the QOL of advance NSCLC patients.